Characteristics of Brain Functional Reorganization and Neuromodulation Strategies in Stroke Patients based on fNIRS - LI Zengyong (康复学报)
Neuroplasticity is essential for the rehabilitation of functional deficits post-stroke. Functional Near Infrared Spectroscopy (fNIRS) is a novel non-invasive brain imaging method capable of assessing changes in oxygenated and deoxygenated hemoglobin concentrations in brain tissue during various task conditions. This allows for the evaluation of cerebral cortex functional dynamics. Due to its straightforward operation, excellent mobility, minimal susceptibility to motion, and reduced subject constraints, this method is well-suited for dynamic evaluation, feedback, and engagement in the rehabilitation of patients with neurological impairments. This provides innovative means for evaluating, predicting therapeutic effects, and guiding rehabilitation plans for stroke patients with motor function disorders. This study provides an overview of fNIRS technology and explores how it is utilized to assess brain function remodeling and implement rehabilitation strategies for stroke patients. The aim is to offer insights for the application of fNIRS technology in functional assessment and neurological rehabilitation for stroke patients. The overview of fNIRS technology includes a brief introduction to the imaging principle, technical advantages, brain function assessment indicators, and the multi-frequency fNIRS brain function analysis model. Using fNIRS, we analyzed the brain function remodeling characteristics in stroke patients to elucidate the patterns and features of brain function remodeling associated with motor dysfunction rehabilitation after stroke. This analysis can offer theoretical insights for the hierarchical rehabilitation management of stroke and the development of specific neural circuit intervention strategies. Through the utilization of fNIRS technology, we have established systematic detection paradigms and evaluation feedback indicators to monitor the brain's specific responses and remodeling processes during rehabilitation interventions. This method enables a deeper understanding of how fNIRS technology supports stroke patient rehabilitation, fosters the development of tailored rehabilitation strategies, and ultimately achieves precise rehabilitation goals.